2022
DOI: 10.2807/1560-7917.es.2022.27.27.2200471
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox outbreak predominantly affecting men who have sex with men, Madrid, Spain, 26 April to 16 June 2022

Abstract: Up to 22 June 2022, 508 confirmed cases of monkeypox (MPX) have been reported in the Madrid region of Spain, 99% are men (n = 503) with a median age of 35 years (range: 18–67). In this ongoing outbreak, 427 cases (84.1%) reported condomless sex or sex with multiple partners within the 21 days before onset of symptoms, who were predominantly men who have sex with men (MSM) (n = 397; 93%). Both the location of the rash, mainly in the anogenital and perineal area, as well as the presence of inguinal lymphadenopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
279
1
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(346 citation statements)
references
References 8 publications
(12 reference statements)
19
279
1
10
Order By: Relevance
“…At the time of data collection, it was not clear whether this Monkeypox epidemic was occurring mainly among men who have sex with men, particularly those with multiple recent partners, as was demonstrated in the subsequent research [ 26 , 32 ]. However, we did not collect this data in our survey, as this was not initially communicated in a clear and documented manner in the evolving literature.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of data collection, it was not clear whether this Monkeypox epidemic was occurring mainly among men who have sex with men, particularly those with multiple recent partners, as was demonstrated in the subsequent research [ 26 , 32 ]. However, we did not collect this data in our survey, as this was not initially communicated in a clear and documented manner in the evolving literature.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other patients with monkeypox, those with HIV infection had higher rates of secondary bacterial infection, more prolonged illness (and thereby also longer period of infectiousness), as well as a higher likelihood of having a confluent or partially confluent rash rather than discrete lesions (22). In contrast, recent reports from European countries where most patients are receiving effective ART have noted no deaths or evident excess in hospitalizations among persons with HIV infection and monkeypox to date (3,4,6). In addition, WHO has stated that a more severe disease course has not been reported in persons with HIV infection who are receiving ART and have a robust immune system (23), a finding supported by recent large cohort studies (5,7,8).…”
Section: Monkeypox In Persons With Hiv Infectionmentioning
confidence: 99%
“…Although anyone in close contact with active cases can be at risk of virus acquisition, the current cases appear to be concentrated among men who have sex with men (MSM) [ 18 , 23 , 24 , 25 , 26 ]. This striking pattern was evident in a recent study on HMPX in London which showed that 196 out of 197 (99.5%) reported cases were identified among MSM (gays and bisexual men) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%